Surgical Strategies to Prevent Adjacent Segment Disease in the Cervical Spine. Issue 3 (April 2019) - Butler, Joseph S.; Morrissey, Patrick B.; Wagner, Scott C.; Kaye, I. David; Sebastian, Arjun S.; Schroeder, Gregory D.; Vaccaro, Alexander R.; Hilibrand, Alan S.
Abstract : The most popular approach to treating symptomatic cervical disk disease is anterior cervical discectomy and fusion. Although this procedure has significant long-term clinical success, it is associated with progressive adjacent segment degeneration with an annual incidence of ∼3%. Total disk arthroplasty was designed as an alternative to fusion that could preserve segmental motion at the operative level and potentially delay or prevent adjacent-level breakdown. The etiology of adjacent segment pathology (ASP) is multifactorial, and it is likely that most cases of ASP are unavoidable. When attempting to surgically prevent ASP, it is important to consider nonfusion alternatives, be judicious in one's level selection, and attempt to restore sagittal alignment. When ASP becomes a clinical problem, it is important to have an algorithm for how best to treat it.